COMPARISON OF OUTCOME (IN TERMS OF RECURRENCE) OF INCISION & DRAINAGE VERSUS ASPIRATION OF BREAST ABSCESS - HASSAN , SSU; HIRAJ , T; NADEEM , A (Biological and Clinical Sciences Research Journal, 2024)
Breast abscesses can lead to significant morbidity and have a negative impact on quality of life. This study aimed to compare recurrence rates after incision and drainage versus aspiration techniques in managing breast abscesses. Objective: To compare the outcome of incision and drainage versus aspiration techniques in managing breast abscesses, specifically recurrence rates. Methods: This study employed a Randomized Controlled Trial design and was conducted at the Department of General Surgery, Nishtar Hospital, Multan, over a period of six months from July 1, 2019, to January 1, 2020. A total of 60 patients meeting the inclusion criteria were randomized into two groups: Group A underwent needle aspiration, while Group B underwent incision and drainage. Both groups received a 10-day course of tab. Ciprofloxacin 500mg BD and tab danzen DS BD. The researcher performed all the procedures. Patients were followed for two weeks, and recurrence of the abscess was recorded as either "yes" or "no". Results: The study included 60 patients with a mean age of 25.58 ± 3.64 years. Of these, 35 (58.3%) were from rural areas and 25 (41.7%) from urban areas. Seventeen (28.3%) patients were unmarried, and 43 (71.7%) were married. The mean body mass index was 25.12 ± 1.97 kg/m2, with obesity present in 7 (11.7%) patients. Thirty-five (58.3%) patients were lactating, with a mean abscess duration of 3.25 ± 0.57 months. The mean abscess size was 1.20 ± 0.18 centimeters, with 55 (91.7%) abscesses ≤ 2 centimeters in size. Diabetes was not present in any patients. Recurrence occurred in 15 (25.0%) patients, with a recurrence rate of 13.3% in Group A and 36.7% in Group B (p = 0.072). Conclusion: The recurrence of breast abscesses was lower in the aspiration group compared to the incision and drainage group. These findings support the use of needle aspiration techniques for the management of breast abscesses. Surgeons treating such patients should consider employing aspiration techniques to achieve better outcomes, thereby reducing the burden of related morbidities and mortalities.